2004
DOI: 10.1080/00365540410020190
|View full text |Cite
|
Sign up to set email alerts
|

Chron's Disease, Rare Association with Selective IgA Immunodeficiency, and Development of Life-threatening Bacterial Infections

Abstract: Life-threatening necrotizing fasciitis and relapsing Lemierre syndrome associated with Fusobacterium necrophorum septicaemia occurred in young adults with a moderate Chron's disease and a missed profound IgA deficiency. This unexpected association of a chronic bowel inflammatory syndrome with prominent IgA abnormalities and severe bacterial infection deserves careful attention by physicians faced with young patients with Chron's disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1
4

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 5 publications
0
1
1
4
Order By: Relevance
“…We found that the concentrations of IgG, but not IgM and IgA, in the patients were significantly higher than that in the HC and correlated positively with the values of Mayo clinic score and the concentrations of serum CRP. Although the IgA deficiency, especially for the lack of secretory component in UC or CD has been reported in several UC cases, we did not observe such deficiency in those 23 UC patients in this population. The difference may stem from a small group of patients we studied.…”
Section: Discussioncontrasting
confidence: 85%
“…We found that the concentrations of IgG, but not IgM and IgA, in the patients were significantly higher than that in the HC and correlated positively with the values of Mayo clinic score and the concentrations of serum CRP. Although the IgA deficiency, especially for the lack of secretory component in UC or CD has been reported in several UC cases, we did not observe such deficiency in those 23 UC patients in this population. The difference may stem from a small group of patients we studied.…”
Section: Discussioncontrasting
confidence: 85%
“…The question of whether IgA deficiency (and in particular lack of the free secretory component)41 predisposes to IBD has been highlighted by several case reports describing association with CD42–44 or UC 41, 45–48. Since the IgA system represents a distinct local immune mechanism in the gut, under constant exposure to bowel antigens, it was postulated that focal deficiency might translate into increased permeability to pyogenic organisms and other antigenic material 49.…”
Section: B‐cell Dysfunctionmentioning
confidence: 99%
“…Пациентка Х., 46 [8][9][10][11][12][13]нормальный уровень IgM (0,98 г/л при норме 0,5 г/л),снижение уровня IgA (до 1,19 г/л при норме 1,1 г/л). В 2011 году при повторном анализе IgG составил 16,0 г/л,98 г/л,12 г/л,что Подведем итоги проведенного обследования.…”
unclassified
“…Причиной терминального илеита часто служит болезнь Крона. Случаи сочетания селективного дефицита IgA и болезни Крона описаны в литературе [12,13]. Вместе с тем диагноз болезни Крона вызывал сомнения, в первую очередь из-за отсутствия яркой клинической картины (не было потери веса, абдоминальной боли; длительный анамнез протекал достаточно спокойно).…”
unclassified
See 1 more Smart Citation